The Possible Role of Art Museums in Regard to Educational Reform - Peter Pivoda (Ksiegarnia Akademicka Publishing, 2019)
This paper concerns ongoing educational reform in Slovakia and its goals as declared in the foundation document entitled Learning Slovakia. Within these goals, we have chosen those which are connected to freedom and supporting concepts of civil society. Besides the political circumstances of reform, we analyse art museums as educational institutions. The aim is to find common interests in education being provided both by schools and art museums, and especially how they may become partners in fulfilling the needs of a new school curriculum. To illustrate one possible way of partnership, we use examples of three individual educational programmes from the Slovak National Gallery in Bratislava.